Encoding extracellular modification of artificial cell membranes using engineered self-translocating proteins - Alexander Harjung; Alessandro Fracassi; Neal K. Devaraj (Nature Communications, 2024)
Abstract The development of artificial cells has led to fundamental insights into the functional processes of living cells while simultaneously paving the way for transformative applications in biotechnology and medicine. A common method of generating artificial cells is to encapsulate protein expression systems within lipid vesicles. However, to communicate with the external environment, protein translocation across lipid membranes must take place. In living cells, protein transport across membranes is achieved with the aid of complex translocase systems which are difficult to reconstitute into artificial cells. Thus, there is need for simple mechanisms by which proteins can be encoded and expressed inside synthetic compartments yet still be externally displayed. Here we present a genetically encodable membrane functionalization system based on mutants of pore-forming proteins. We modify the membrane translocating loop of α-hemolysin to translocate functional peptides up to 52 amino acids across lipid membranes. Full membrane translocation occurs in the absence of any translocase machinery and the translocated peptides are recognized by specific peptide-binding ligands on the opposing membrane side. Engineered hemolysins can be used for genetically programming artificial cells to display interacting peptide pairs, enabling their assembly into artificial tissue-like structures.